2020
DOI: 10.1177/1403494820929833
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in young Syrian refugees recently resettled in Norway

Abstract: Aims: Millions have fled from the civil unrest in Syria, and half of these are children and youth. Although they are a population with an elevated risk of health problems due to adverse pre-migratory and post-migratory experiences, few studies have explored their health-related quality of life (HRQoL). This is considered a fundamental construct in public health and might provide complementary descriptions of their health and well-being after resettling in a new country. Methods: This was a cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
4
9
0
Order By: Relevance
“…The general gender pattern of girls reporting lower HRQoL in the EU reference population is coherent with the pattern seen among refugee minors in the present study, though the gap was smaller and there was some variability depending on the specific dimensions and when adjusting for socioeconomic characteristics. In a study of young Syrian refugees resettled in Norway similar results were found, where being female was associated with a lower HRQoL Index and psychological wellbeing scores [46]. A gradual decrease in mean scores for all dimensions of HRQoL with increasing age in the Norwegian sample was also comparable to our finding that minors aged 12-15 had significantly higher HRQoL scores compared to minors aged 16-18. Moreover, minors who fled to Sweden unaccompanied scored significantly lower HRQoL scores compared to minors who came to Sweden accompanied.…”
Section: Discussionsupporting
confidence: 89%
“…The general gender pattern of girls reporting lower HRQoL in the EU reference population is coherent with the pattern seen among refugee minors in the present study, though the gap was smaller and there was some variability depending on the specific dimensions and when adjusting for socioeconomic characteristics. In a study of young Syrian refugees resettled in Norway similar results were found, where being female was associated with a lower HRQoL Index and psychological wellbeing scores [46]. A gradual decrease in mean scores for all dimensions of HRQoL with increasing age in the Norwegian sample was also comparable to our finding that minors aged 12-15 had significantly higher HRQoL scores compared to minors aged 16-18. Moreover, minors who fled to Sweden unaccompanied scored significantly lower HRQoL scores compared to minors who came to Sweden accompanied.…”
Section: Discussionsupporting
confidence: 89%
“…Syrians were the largest group of forced migrants to enter Norway at the time of the study, and 5553 were registered in the age groups recruited in 2018 [ 25 ]. The inclusion criterion for age was 12–24 years, as they have the right to attend secondary and upper secondary schools.…”
Section: Methodsmentioning
confidence: 99%
“…Syrians were the largest group of forced migrants to enter Norway at the time of the study, and 5553 were registered in the age groups recruited in 2018 [25].…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…With regards to relevant risk exposure for refugee children and youth, experiences from war and flight—such as violence, seeing someone die, or fearing for one's life—are commonly reported among refugee children, including Syrian youth ( 30 ). These PTEs are repeatedly associated with negative outcomes, such as increased mental distress ( 7 , 8 ) and reduced quality of life ( 29 , 31 ). In addition, studies suggest that risk factors after settlement— post-migration stressors— may impact health and wellbeing above and beyond those of PTEs, even more prominently so in children and youth ( 32 , 33 ).…”
Section: Introductionmentioning
confidence: 99%